Trends of stress and stress coping in patients with atopic dermatitis: Analysis using the brief coping orientation to problems experienced inventory - Sakae Kaneko; Yasuyuki Sumikawa; Hiroyuki Murota; Mayuko Tabara; Ichiro Katayama; Eishin Morita (Frontiers Media S.A., 2020)
Abstract Background The nature of the stress experienced by adult atopic dermatitis (AD) patients is not fully understood. Objectives We investigated the experience of stress in these patients and their coping methods using a questionnaire. Methods Fifty‐one AD patients under the care of the Department of Dermatology at Shimane University Hospital and 50 AD patients under the care of the Department of Dermatology at Sapporo Medical University Hospital were surveyed. The Brief Coping Orientation to Problems Experienced (COPE) inventory was used to examine coping. Results The most common cause of stress associated with AD was work, followed by the presence of allergy symptoms and being ill. The patients reported using positive coping methods such as self‐distraction and humor, and negative coping methods such as behavioral disengagement and self‐blame. Women used coping methods significantly more often than men, and patients aged 30 years and older used alcohol as a coping strategy more often than younger patients. Patients with severe conditions used coping methods less frequently. A group that experienced stress often used positive reframing less frequently, but more often used methods such as emotional support, substance use, behavioral disengagement, and self‐blame. Conclusions We observed differences in stress coping based on gender, age, severity of AD symptoms, severity of stress, and how stress was experienced, which highlights the importance of dealing with stress in ways that take the AD patient's characteristics into consideration.